Functional classification of isolated zygomatic arch fracture: new proposal (2021)
Isolated zygomatic arch fractures are common fractures in maxillofacial trauma. These fractures can trigger a functional alteration in the mouth opening and closing. Until now, there is no published classification of an isolated zygomatic arch fracture that contains the presence or not of coronoid impingement. So we propose a new classification that is easy to handle and has the largest number of scenarios that can occur in this type of fracture. The isolated zygomatic arch fracture is classified as Type I: Nondisplaced fractures, Type II: Greenstick fracture with or without coronoid impingement, Type III: Single displaced fracture with or without coronoid impingement, Type IV: Multiple displaced fracture with or without coronoid impingement, Type V: Comminuted fracture with or without coronoid impingement. We consider it to be a comprehensive classification, with general concepts of bone fractures, that can be incorporated into professional daily practice.